1995
DOI: 10.1002/ldr.3400060404
|View full text |Cite
|
Sign up to set email alerts
|

Soil degradation by Erosion of a typic hapludalf in central Ohio and its rehabilitation

Abstract: Soil erosion and runoff were monitored from 1988 to 1990 on a Miamian soil (Typic Hapludalf) of 5‐6 per cent slope using field runoff plots. Four treatments were studied: (i) disk‐plough up and down the slope to 0.3 m depth (DP); (ii) disk‐plough up and down the slope followed by a protective netting (PN); (iii) uncultivated fallow without any vegetation followed by surface soil removal (R); (iv) uncultivated fallow with natural vegetation followed by ploughing (F). Mean annual runoff losses were 6, 114 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…At site 2, however, the SOC concentration for soil removal and undisturbed treatments were lower and statistically similar to the soil addition treatment for 10-to 30-cm (4-to 12-in) depth. The adverse effect of erosion-induced topsoil loss on SOC concentration has been widely reported in different soil types and locations (Changere and Lal 1995;Lal 1998;Wairiu and Lal 2003;Fenton et al 2005;Oyedele and Aina 2006). The mean SOC concentration in our study, across all TSD levels, was significantly affected by the amendment type (table 1), being higher in 0-to 10-cm (0-to 4-in) depth for soils treated with organic amendments at both sites: 29.0 g kg -1 versus 20.8 g kg -1 for site 1 and 25.8 g kg -1 verus 15.2 g kg -1 for site 2.…”
Section: (A)mentioning
confidence: 99%
“…At site 2, however, the SOC concentration for soil removal and undisturbed treatments were lower and statistically similar to the soil addition treatment for 10-to 30-cm (4-to 12-in) depth. The adverse effect of erosion-induced topsoil loss on SOC concentration has been widely reported in different soil types and locations (Changere and Lal 1995;Lal 1998;Wairiu and Lal 2003;Fenton et al 2005;Oyedele and Aina 2006). The mean SOC concentration in our study, across all TSD levels, was significantly affected by the amendment type (table 1), being higher in 0-to 10-cm (0-to 4-in) depth for soils treated with organic amendments at both sites: 29.0 g kg -1 versus 20.8 g kg -1 for site 1 and 25.8 g kg -1 verus 15.2 g kg -1 for site 2.…”
Section: (A)mentioning
confidence: 99%
“…It is only the decline in organic C and pH that seems to be erosion induced, as there are more plots with a low degree of cover that are affected (Table 6). Chengere and Lal (1995) also found that temporal changes in soil chemical properties seemed to take place independent of treatment. Such changes can possibly be attributed to leaching or mineralization.…”
Section: Erosionõs Impact On the In Situ Soilmentioning
confidence: 82%
“…Olson and Nizeyimana (1988) observed an increase in clay content in eight eroded soils throughout Illinois, while Chengere and Lal (1995) also reported an increase in clay content after removal of the surface 20 cm of a silty clay loam soil to simulate severe erosion. This increase in clay content in the Ap horizon is attributed to the exposure and subsequent mixing by tillage operations of lower soil horizons (B) rich in clay.…”
Section: Introductionmentioning
confidence: 92%